5-Aminosalicylic acid, a specific drug for ulcerative colitis. (August 2015) - Hauso, Øyvind; Martinsen, Tom Christian; Waldum, Helge
Abstract Objective. The etiology of the inflammatory bowel diseases is unknown, although genetic factors play a role, and tobacco smoking has opposite effect on the two entities. Inflammation is central in the pathogenesis, and treatment is aiming to suppress it. The active part of salazopyrin, the oldest drug in use in the treatment of ulcerative colitis, is 5-aminosalicylic acid (5-ASA). In the present paper, we wanted to discuss the etiology and pathogenesis of ulcerative colitis in relation to the beneficial effects of 5-ASA and particularly whether this compound has a specific effect on ulcerative colitis. Methods/Results. 5-ASA seems to have a selective positive effect on ulcerative colitis in inducing remission, preventing relapse and possibly reducing the risk of cancer. In contrast to other agents used in the treatment of ulcerative colitis, 5-ASA does not have any known anti-inflammatory effect on other organs or other colonic inflammatory diseases like diverticulitis. Moreover, the effect on experimental colitis in rodents is not convincing. Conclusion. 5-ASA seems to have a specific effect on the inflammation in ulcerative colitis. Research on the mechanism of its action may give information on the etiology of ulcerative colitis. 5-ASA is a first-line treatment that should be given once daily in high doses and for long term to reduce the possibility of recurrence and risk of colonic cancer. Side effects with 5-ASA are rare, and every patient with ulcerative colitis who tolerate this drug, should be treated with 5-ASA.